The relationship between technology, work-life balance, and employee performance as perceived by the employees of EJAPKI General Services, Inc. from the Operations Department - Bayron, Franz Nathaniel A. (Animo Repository, 2023)
This study explores the perceived relationship between technology, work-life balance, and employee performance among the employees of EJAPKI General Services Inc., specifically focusing on the Operations Department. The objective is to assess the extent and specific ways in which qualitative interviews conducted with employees of EJAPKI contribute to a deeper and more intricate comprehension of the relationship between technology, work-life balance, and employee performance. The study also seeks to explore the qualitative insights gained from these interviews, focusing on the ways in which they enhance our understanding of the complexities involved in this relationship. The research methodology involves surveying a sample of employees from the Operations Department using a Likert-scale questionnaire consisting of items that measure thr employees' perceptions of technology usage, work-life balance, and their own performance. Statistical analyses, such as correlation, regression, and pattern matching are employed to analyze the data and draw conclusions. Preliminary findings reveal that work-life balance is a significant variable impacting employee performance within the Operations Department. Employees who reported higher levels of work-life balance also exhibited better performance. On the other hand, technology was found to be insignificant in relation to employee performance, suggesting that other factors may have a more substantial influence. These findings shed light on the importance of promoting work-life balance within the Operations Department at EJAPKI General Services Inc. Hence, management should focus on implementing policies and practices that support work-life balance to enhance employee performance. Additionally, further exploration of the factors influencing employee performance beyond technology is recommended for a comprehensive understanding of the topic. Keywords: Work-Life Balance, Technology, Employee Performance, Service Sector, Operations